If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (7x + -32) + (5x + -27) = (9x + -8) Reorder the terms: (-32 + 7x) + (5x + -27) = (9x + -8) Remove parenthesis around (-32 + 7x) -32 + 7x + (5x + -27) = (9x + -8) Reorder the terms: -32 + 7x + (-27 + 5x) = (9x + -8) Remove parenthesis around (-27 + 5x) -32 + 7x + -27 + 5x = (9x + -8) Reorder the terms: -32 + -27 + 7x + 5x = (9x + -8) Combine like terms: -32 + -27 = -59 -59 + 7x + 5x = (9x + -8) Combine like terms: 7x + 5x = 12x -59 + 12x = (9x + -8) Reorder the terms: -59 + 12x = (-8 + 9x) Remove parenthesis around (-8 + 9x) -59 + 12x = -8 + 9x Solving -59 + 12x = -8 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -59 + 12x + -9x = -8 + 9x + -9x Combine like terms: 12x + -9x = 3x -59 + 3x = -8 + 9x + -9x Combine like terms: 9x + -9x = 0 -59 + 3x = -8 + 0 -59 + 3x = -8 Add '59' to each side of the equation. -59 + 59 + 3x = -8 + 59 Combine like terms: -59 + 59 = 0 0 + 3x = -8 + 59 3x = -8 + 59 Combine like terms: -8 + 59 = 51 3x = 51 Divide each side by '3'. x = 17 Simplifying x = 17
| -20x+20y=-20 | | -5-4z=-5z+5 | | x/2-12=4 | | z^4+0.5z+1=0 | | (13x-11)+(4x+1)=(18x-15) | | 5k=4K-6 | | -3+10h=7h+6 | | (9x-8)+x=180 | | (3a+2)=-8 | | -9x+y=-22 | | 8b+8=6b | | x+3x-4=6 | | 2lne^5=y | | 7x+54+42=180 | | 0.60x=12 | | 9s=-1+10s | | -6+5w=6w | | -26=-6+4v | | -8t-2=-9t | | 3x^2-32x=-65 | | x+.25x=75 | | 2x-1=1.7 | | 2x^2+20x+70=0 | | Ptanx+qtanx=tanz | | 9x-4+122=180 | | (8+3)4=8*4+3*4 | | 45j+-36j-3j-45=-87 | | (4x-22)+(10x-4)+(x+11)=180 | | -8a+14b+61=0 | | 2z-z+2z-z-2=18 | | 3x+7y=-10 | | (9x+3)+(5x-2)+(11x-21)=180 |